Species circumscription of the Caltha leptosepala polyploid complex (Ranunculaceae) based on molecular and morphological data - Wefferling, Keir M.; Hoot, Sara B. (Phytotaxa, 2017)
The Caltha leptosepala species complex (Ranunculaceae) is taxonomically unresolved, with authors of various regional floras recognizing different names and numbers of species. Integrating molecular, morphological, cytological, and geographic data, we describe three species in the complex, restoring two species names, C. biflora and C. chionophila, in addition to recognizing C. leptosepala. Based on chloroplast and nuclear ribosomal phylogenies, we illustrate key morphological synapomorphies for the three Caltha species, assess the usefulness of previously used morphological characters, and provide a dichotomous key for their field identification. A neotype is designated for C. leptosepala var. howellii because the originals were lost or destroyed.